An evolutionary planning method for distribution networks considering prosumers and shared energy storage - Han, Jinglin; Feng, Xichun; Chen, Zhiyong; Hu, Ping; Zhao, Hui; Chen, Yubing; Liu, Nian (Frontiers in Energy Research, 2024)
This research provides a rolling planning method for distribution networks, that takes into account shared energy storage capacity configuration and grid topology optimization due to the stochastic unpredictability of the planning scenarios and the interaction between multi-agents. Firstly, the grid topology and the investment capacity of the shared energy storage are optimized with the aim of minimizing the overall cost within the planning time scale of the grid company, and a distribution network planning model that precisely satisfies the reliability requirements is built. Secondly, the operational utility model of prosumers is suggested based on the planning strategy of the grid company. The cooperation of grid company corporations with prosumers is established in the evolutionary game model. The differential evolution algorithm is utilized to realize the dynamic solution of the planning strategy by creating the replicator dynamic equation of the grid firm population. Taking the IEEE-33 bus system as an example for simulation analysis, to demonstrate the usefulness of the suggested evolution game-based planning model, which can lower network planning costs and system operating costs while optimizing prosumers' load curves.